A Study on Effectiveness of Learning through Apps and Classroom among Higher Secondary School Students in Chennai District - Deo, Sarah; Selvakumar, Y Stanly (Journal of Advanced Research in English & Education, 2022)
This paper centres on how educational apps came to be a standard fare for online instruction. It takes into account the current pandemic scenario that completely altered the educational landscape. The elements of the educational process that we regard to have the capacity to influence the outcome elements are referred to as institutional factors. The outcomes variables put the students' assessments of the course into practical terms. According to the findings of this study, the course design and learning content or material are the most influential variables for learner satisfaction and perceived learning among the other institutional variables studied. How to cite this article: Deo S, Selvakumar YS. A Study on Effectiveness of Learning through Apps and Classrooms among Higher Secondary School Students in Chennai District. J Adv Res Eng & Edu 2022; 7(2): 1-3. DOI: https://doi.org/10.24321/2456.4370.202208